Design and evaluation of a new mobile application to improve the management of minor ailments: a pilot study - Ehab Mudher Mikhael; Fadya Yaqoob Al-Hamadani; Ali Mohammed Hadi (BMC, 2022)
Abstract Background Seeking pharmacist advice about minor ailments is a common practice among Iraqi patients because such advice is free and quick. Unfortunately, the assessment and management of minor ailments by Iraqi pharmacists were inappropriate. Therefore, this study aimed to develop a model for a mobile application that can assist community pharmacists in the diagnosis and management of minor ailments. Methods The scientific content of the application was based on the information in the symptoms in the pharmacy and British National Formulary books. The design and content of the application were approved by two experts. Thereafter, the application was built for Android mobiles using flutter technology and dart language. A pre-post pilot study was conducted to assess outcomes associated with use of the application, including user acceptance and appropriateness of clinical recommendations. Fifteen students from the College of Pharmacy/University of Baghdad who had an Android mobile participated in this study. Two different scenarios about diarrhea were used during the pilot study, in which the researcher acted as a patient (SP) and the participant student as a pharmacist. Results After using the application, the number of questions asked by the participated student to the SP was significantly increased to about double. Additionally, providing the SP with appropriate non-pharmacological and pharmacological therapy along with optimum counseling and education were also significantly improved. All study participants agreed on the application's ease of use and ability to reduce diagnosis and medication errors. Conclusions The implementation of the newly developed mobile application, diarrhea management step by step, was associated with improvements in assessment and recommended treatments for diarrhea cases with good acceptance by a pilot sample of pharmacy students at Baghdad University.